Dystocia in Dairy Cows and Heifers: A Review with a Focus on Future Perspectives - Angeliki Tsaousioti; Athina Basioura; Anastasia Praxitelous; Georgios Tsousis (Dairy)
Dairy cow management has evolved tremendously in recent decades, particularly regarding reproductive techniques. The widespread adoption of synchronization protocols, sexed semen, beef semen in dairy cows, reproductive biotechnologies such as in vivo-derived (IVD) or in vitro-produced embryos (IVP), and precision livestock farming is transforming the daily practices of dairy farmers and veterinarians. These implementations are typically adapted in different ways when applied to the breeding of heifers or cows. Considering these developments, dystocia—a significant welfare and productivity concern—may warrant reevaluation. The aforementioned changes are likely to have a substantial impact on its prevalence, severity, and outcome. This review aims to address the main aspects of dystocia in dairy cows and heifers, with a particular focus on the potential impact of recent advances in reproductive and calving management.